2005
DOI: 10.1007/s10557-005-6894-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sildenafil on Reperfusion Function, Infarct Size, and Cyclic Nucleotide Levels in the Isolated Rat Heart Model

Abstract: (1) Pretreatment with low concentrations of sildenafil (20-50 nM) improves, while higher concentrations (200 nM) worsen reperfusion function in this model. (2) Low concentrations of sildenafil (20-50 nM) decrease infarct size while the higher concentrations had no effect. (3) These protective properties of low concentrations of sildenafil may be related to its cGMP elevating and cAMP suppressing effects in the ischaemic heart. (4) Possible end-effectors for sildenafil in the ischaemic heart include the mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
38
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 24 publications
11
38
1
2
Order By: Relevance
“…24 The PDE 5 inhibitor sildenafil decreases infarct size, and this protection is associated with increased myocardial cyclic guanosine monophosphate and reduced cAMP levels in isolated rat hearts. 25 On the whole, the by-now well-founded concept of localized signaling through cAMP provides an attractive avenue for more specific drug therapy and, in the present study by Takahasi et al, 5 provides a potential explanation for an additive protection by AC overexpression and propranolol.…”
Section: Article P 388mentioning
confidence: 55%
“…24 The PDE 5 inhibitor sildenafil decreases infarct size, and this protection is associated with increased myocardial cyclic guanosine monophosphate and reduced cAMP levels in isolated rat hearts. 25 On the whole, the by-now well-founded concept of localized signaling through cAMP provides an attractive avenue for more specific drug therapy and, in the present study by Takahasi et al, 5 provides a potential explanation for an additive protection by AC overexpression and propranolol.…”
Section: Article P 388mentioning
confidence: 55%
“…By selectively inhibiting phosphodiesterase type-5 (PDE-5) and thus effectively reducing the breakdown of cGMP, sildenafil administration can markedly improve pulmonary and cardiac functional capacity, and hemodynamics (du Toit et al, 2005;Traverse et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…9 This is supported by compelling evidence from animal models indicating that the PDE5is such as sildenafil, tadalafil and vardenafil are cardioprotective in ischaemia-reperfusion injury (IRI) while suppressing cardiac arrhythmias and improving cardiac function. [10][11][12][13][14][15] Furthermore, small randomised controlled trials (RCTs) in systolic heart failure have shown an improvement in haemodynamic parameters and functional indices. 16 It is therefore important to establish whether there is benefit or harm in highrisk patients with ED.…”
mentioning
confidence: 99%